Comparative mathematical study of MHD mixed convection flow of nano-fluids in the existence of porous media, heat generation and radiation through upstanding equidistant plates. (2021) - Mehta, Ruchika; Jangid, Sanju; Kumar, Manoj
Abstract: Intention of current work is to examine impacts of radiation and heat generation in time-dependent MHD assorted convection flow of nano-fluids along a erect channel concluded permeable medium. Tetrad kinds of nanofluids were considered (i) Water based – Cu (ii) Water created – Ag (iii) Water created – Al2 O3 (iv) Water created – TiO2. Water is occupied as convectional base liquid and Ag, Cu, Al2 O3, TiO2 elements are combined in this base liquid. Care in attention the clustering and Brownian motion of Kleinstreuer, Koo and nanoparticles sample is applied. The chief features of the nano-fluids have better thermo physical cretic such as high thermal conductivity, minimal clogging in movement passageway, long term stability and homogeneity. The main border layer calculations are expressed and diminished to a set of ordinary differential equations using perturbation method. Analytical resolutions are gotten for velocity and temperature, deliberated and proper outcomes are exposed through graphs. The conclusion of the work may be valuable for usage in the arena of science & Technology. Present study emphasis on comparative mathematical study of MHD mixed convection flow of four type of nano-fluids. This comparative study is carried out in the presence of porous media, heat generation and radiation effect.